Degradable low-immunogenic biological anti-adhesion material, preparation method, application and biological repair patch thereof

By extracting and processing the decellularized matrix from the sublayer tissue of the small intestine of animals, a low-immune origin biological anti-adhesion material was prepared, which solved the problems of long degradation time and DNA residue in the existing materials, and achieved rapid degradation, low immune response and excellent anti-adhesion effect.

CN119326954BActive Publication Date: 2025-03-28ABORIMEI (CHENGDU) MEDICAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411917233.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Existing biological anti-adhesion materials have a long degradation time in vivo and have animal-derived DNA residues, which may trigger immune rejection and other complications.

Method used

A low-immune source biological anti-adhesion material was prepared by extracting the decellular matrix from the submucosal tissue of the animal's small intestine, and performing cleaning, inactivation, mechanical treatment, soaking in aqueous acetic acid solution and freeze-drying.

Benefits of technology

The material has rapid degradability, low immunogenicity and good biocompatibility, and can completely degrade in the body, reduce postoperative immune response, and provide excellent anti-adhesion effect and wound healing support.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119326954B_ABST
    Figure CN119326954B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of biomaterials for medical devices, and specifically relates to a biodegradable low-immunogenic anti-adhesion material, a preparation method thereof, an application thereof, and a biorepair patch. The present invention pre-treats, removes antigens, and freeze-dries porcine small intestine to obtain a biodegradable immunogenic anti-adhesion material. The preparation process is stable, and the product is easy to store. The material has suitable mechanical properties, excellent anti-antigen effect, and a DNA residue of 24ng / g. When the material is used for postoperative adhesion prevention in the abdominal cavity, it has good biocompatibility and low immunogenicity, and will not cause obvious postoperative immune response after implantation; it has good fitting performance, and does not require suture fixation after fitting the wound; it has degradable absorbability and can be completely degraded within four weeks; it has a good anti-adhesion effect and is an excellent biodegradable anti-adhesion material. It has promoted the application of decellularized matrix materials in implantable medical materials, and has a good prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of medical device biomaterials, and in particular relates to a degradable low-immunogenic biological anti-adhesion material, a preparation method and application thereof, and a biological repair patch. Background Art

[0002] Pelvic and abdominal adhesions refer to abnormal adhesions formed between tissues or organs in the pelvic and abdominal cavities. Adhesions are usually caused by surgery, inflammation or injury and are common. Almost all abdominal surgeries, whether open or laparoscopic, will cause varying degrees of pelvic and abdominal adhesions. This adhesion can lead to adhesions between organs, affecting normal function and may cause symptoms such as abdominal pain, chronic pain, intestinal strangulation, intestinal obstruction or infertility. Therefore, the problem of postoperative pelvic and abdominal adhesions has received increasing attention. How to reduce or avoid the formation of adhesions has become an important issue.

[0003] At present, there are two ways to prevent postoperative adhesion at home and abroad, one is drug treatment, and the other is physical anti-adhesion and anti-adhesion membranes of instruments. The anti-adhesion materials used in surgical treatment mainly include two categories: non-degradable absorbable materials and degradable absorbable materials: non-absorbable materials such as polytetrafluoroethylene and cellulose anti-adhesion membranes, although they effectively inhibit the occurrence of adhesion and the risk of secondary surgery, the continued presence of such non-degradable materials will lead to inflammatory reactions and fibrosis of surrounding organs and tissues, which is not conducive to the secondary surgery; biodegradable diaphragm materials are widely used in surgery, including such as sodium hyaluronate-carboxymethyl cellulose, chitosan, oxidized regenerated cellulose, polylactic acid and other polymer materials, however, various materials have some disadvantages, such as chitosan but the mechanical strength is not large enough, the degradation cycle is unstable, polylactic acid has poor adhesion to the wound surface, and slow degradation. Considering the shortcomings of the above materials, new biomaterials need to be developed for anti-adhesion.

[0004] Since anti-adhesion biomaterials are particularly critical to anti-adhesion effects and degradation cycles, the tissue adhesion and mechanical properties of the material are also the key to the anti-adhesion effect. Appropriate tissue adhesion and mechanical properties can make the material difficult to fall off during the healing process of the wound, which can effectively prevent adhesion and facilitate normal wound healing. Therefore, a biological anti-adhesion material with appropriate tissue adhesion, certain mechanical properties, appropriate in vivo retention time, and good biocompatibility is needed.

[0005] Small intestinal submucosa (SIS) is a natural cell matrix biomaterial, usually prepared from porcine small intestine. The invention patent (CN106983918B) discloses a degradable biological anti-adhesion material, which uses the small intestinal submucosa tissue of animals as raw materials. After removing the immunogenicity, it can be used for anti-adhesion treatment of wounds. However, there are still some problems with this material: 1. The degradation time in the body is long, which takes 1-3 months; 2. Animal-derived DNA is difficult to completely remove, and the residual DNA is 10ng / mg. Clinical studies have shown that decellularized matrix material products may have complications such as serous swelling, infection, and immune rejection, among which serous swelling has the highest incidence. Studies have shown that serous swelling is closely related to the residual animal-derived DNA of the product.

[0006] Therefore, it is still necessary to construct a biological anti-adhesion material that is rapidly degradable and has low immunogenicity. Summary of the invention

[0007] In view of the defects of the prior art, the present invention provides a biological anti-adhesion material, the purpose of which is to construct a biological anti-adhesion material that can be rapidly degraded and has low immunogenicity.

[0008] The present invention provides a degradable low-immunogenic biological anti-adhesion material, which is prepared by a method comprising the following steps:

[0009] Step 1, taking the small intestinal submucosal tissue of the animal, washing, inactivating, and mechanically treating it;

[0010] Step 2, washing the material of step 1, soaking it in an organic solvent and an acetic acid aqueous solution respectively, and then washing it to obtain a decellularized matrix fresh film;

[0011] Step 3, freeze-drying the acellular matrix fresh film to obtain;

[0012] The immersion time in the acetic acid aqueous solution is 10-20 hours;

[0013] The freeze-drying procedure is: pre-freeze to -50~-40°C under non-vacuum, and keep warm for 0.8-1 minute; then start the vacuum, adjust the temperature to -40~-35°C, and keep warm for 0.8-1 minute; adjust the temperature to -30~-25°C, and keep warm for 0.8-1 minute; adjust the temperature to -22~-18°C, and keep warm for 0.8-1 minute; adjust the temperature to -10~-5°C, and keep warm for 0.8-1 minute; adjust the temperature to -2~2°C, and keep warm for 0.8-1 minute; adjust the temperature to 10~15°C, and keep warm for 0.8-1 minute; adjust the temperature to 20~25°C, and keep warm for 0.8-1 minute; adjust the temperature to 25~35°C, and keep warm for 0.8-1 minute.

[0014] Preferably, the concentration of the acetic acid aqueous solution is 1.8-2.2 mol / L, and the immersion time in the acetic acid aqueous solution is 15 hours.

[0015] Preferably, the organic solvent is a mixed solvent of methanol and chloroform in a volume ratio of 1:1-1.2, the volume of the organic solvent is 2-6 L, and the immersion time in the organic solvent is 120±10 minutes.

[0016] Preferably, the volume of the organic solvent is 6L.

[0017] Preferably, the animal's small intestinal submucosal tissue may also be bovine pericardium or amnion.

[0018] Preferably, in step 1, the cleaning is cleaning with water, the inactivation is soaking in a peracetic acid solution with a mass fraction of 2.9% to 3.2% for 90 to 120 minutes, and the mechanical treatment is mechanically removing the muscle layer and the serosal layer;

[0019] And / or, in step 2, the cleaning is performed by washing with water and ultrasonically treating the mixture at a power of 280-300 W for 20-60 minutes.

[0020] Preferably, the biological anti-adhesion material has a DNA residue of 22.9-85.2 ng / g, a fat residue mass percentage of 0.85-8.8%, a breaking strength of 1.9-3.3N, a breaking elongation of 17.3-26.9N, and a bursting strength of 14.3-21.9N.

[0021] The present invention provides a method for preparing any of the above-mentioned biological anti-adhesion materials, which comprises the following steps:

[0022] Step 1, taking the small intestinal submucosal tissue of the animal, washing, inactivating, and mechanically treating it;

[0023] Step 2, washing the material of step 1, soaking it in an organic solvent and an acetic acid aqueous solution respectively, and then washing it to obtain a decellularized matrix fresh film;

[0024] Step 3, freeze-drying the acellular matrix fresh film to obtain;

[0025] The immersion time in the acetic acid aqueous solution is 10-20 hours;

[0026] The freeze-drying procedure is: pre-freeze to -50~-40°C under non-vacuum, and keep warm for 0.8-1 minute; then start the vacuum, adjust the temperature to -40~-35°C, and keep warm for 0.8-1 minute; adjust the temperature to -30~-25°C, and keep warm for 0.8-1 minute; adjust the temperature to -22~-18°C, and keep warm for 0.8-1 minute; adjust the temperature to -10~-5°C, and keep warm for 0.8-1 minute; adjust the temperature to -2~2°C, and keep warm for 0.8-1 minute; adjust the temperature to 10~15°C, and keep warm for 0.8-1 minute; adjust the temperature to 20~25°C, and keep warm for 0.8-1 minute; adjust the temperature to 25~35°C, and keep warm for 0.8-1 minute.

[0027] The present invention also provides use of any of the above-mentioned biological anti-adhesion materials in preparing implantable medical materials, wherein the implantable medical materials include abdominal repair patches, oral repair patches, pelvic floor repair patches, and hernia repair patches.

[0028] The present invention also provides a biorepair patch with low immunogenicity, characterized in that it is obtained by using any of the above-mentioned bio-anti-adhesion materials as active substances and adding pharmaceutically acceptable excipients or auxiliary components.

[0029] The present invention provides a biodegradable, low-immunogenic anti-adhesion material. The porcine small intestine is pretreated, deantigenized, and freeze-dried to obtain a decellularized matrix material. The preparation process is stable and the product is easy to store. The material has suitable mechanical properties, excellent deantigenization effect, and a DNA residue of 24ng / g. When the material is used for postoperative adhesion prevention in the abdominal cavity, it has good biocompatibility and low immunogenicity, and will not cause obvious postoperative immune response after implantation; it has good biomechanical properties and good fitting properties, and does not require suture fixation after fitting the wound. It has degradable absorbability and can be completely degraded within four weeks. It has good anti-adhesion effect in preventing adhesion in the abdominal cavity of animals and is an excellent degradable bio-anti-adhesion material. It promotes the application of decellularized matrix materials in implantable medical materials and has a good prospect.

[0030] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0031] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1This is a diagram of the biological anti-adhesion material prepared in the example.

[0033] Figure 2 The following are pictures of the adhesion between the uterus and bladder of New Zealand rabbits in each group. a) The picture shows the adhesion between the uterus and bladder of New Zealand rabbits in the negative control group 4 weeks after modeling; b) The picture shows the adhesion between the uterus and bladder of New Zealand rabbits in the positive control group 4 weeks after modeling; c) The picture shows the adhesion between the uterine bleeding site and the anti-adhesion material of the New Zealand rabbits in the experimental group just after the anti-adhesion material was implanted; d) The picture shows the adhesion between the uterus and bladder of the New Zealand rabbits in the experimental group 4 weeks after the anti-adhesion material was implanted. DETAILED DESCRIPTION

[0034] In the following examples and experimental examples, reagents and materials not particularly described are all commercially available.

[0035] Example 1 Biological anti-adhesion material and preparation method thereof

[0036] The biological anti-adhesion material of this embodiment is prepared by the following method:

[0037] The raw material of the biological anti-adhesion material is selected from the submucosal layer of the small intestine of pigs, and the acellular matrix fresh film is obtained through pretreatment, antigen removal and washing, and then freeze-dried, cut, packaged and sterilized.

[0038] 1. Preprocessing

[0039] (1.1) Cleaning: Wash fresh pig small intestine repeatedly with purified water.

[0040] (1.2) Inactivation: Soak the cleaned raw materials in 3% peracetic acid solution (solvent is water) for 90 minutes.

[0041] (1.3) Mechanical treatment: The soaked material is cleaned with purified water, and the muscle layer and serous layer of the material are initially removed by mechanical methods.

[0042] 2. Antigen removal

[0043] (2.1) Ultrasonic cleaning: Place the pretreated material in a container filled with purified water and clean it with ultrasound for 20 minutes (ultrasonic power 300W).

[0044] (2.2) Degreasing: The cleaned material was placed in an oscillator and degreased with 6 L of a mixed solvent of methanol and chloroform in a volume ratio of 1:1 for 2 hours.

[0045] (2.3) Decellularization: The defatted material was placed in 2 L of 2 mol / L acetic acid solution (solvent: water) for 15 h for decellularization.

[0046] (2.4) Cleaning: Place the treated material in a container filled with purified water, clean it with ultrasound for 60 minutes (ultrasonic power 300W), and then clean it with injection water to obtain a decellularized matrix fresh film.

[0047] 3. Freeze drying

[0048] The decellularized matrix fresh film is spread evenly, and the air in the unattached part is exhausted. The decellularized matrix fresh film is freeze-dried using the freeze-drying conditions in Table 1 to finally obtain the decellularized biomaterial, such as Figure 1 As shown, the thickness is 1-5 μm.

[0049] Table 1 Freeze drying conditions

[0050]

[0051] 4. Cutting and packaging

[0052] The freeze-dried decellularized matrix material is cut and packaged according to different specifications.

[0053] 5. Sterilization

[0054] The packaged decellularized matrix material is irradiated with gamma rays.

[0055] Example 2 Biological anti-adhesion material and preparation method thereof

[0056] The preparation method of Example 1 was followed, except that the amount of the mixed solvent of methanol and chloroform used in the degreasing step was 2 L, and the decellularization time was 10 h.

[0057] Example 3 Biological anti-adhesion material and preparation method thereof

[0058] The preparation method of Example 1 was followed, except that the amount of the mixed solvent of methanol and chloroform used in the degreasing step was 4 L, and the decellularization time was 20 h.

[0059] The technical solution of the present invention is further described below through experiments. The biological anti-adhesion material samples tested in the following experimental examples are prepared by the method of Example 1.

[0060] The method for constructing the model animal of postoperative abdominal adhesion is as follows:

[0061] (1) Preoperative preparation: New Zealand rabbits (source: Sichuan Provincial Experimental Animal Committee Farm) were anesthetized with 30 mg / kg sodium pentobarbital. The animals were tied to the operating table in a supine position, the abdominal hair was shaved, and the lower abdominal skin was disinfected with iodine and 75% alcohol respectively. A 4 cm long longitudinal incision was made on the right side of the lower abdomen (above the uterus) to examine the right uterus and fallopian tube.

[0062] (2) Creation of wound: New Zealand rabbits were divided into three groups: negative control group, positive control group, and experimental group, with at least 6 New Zealand rabbits in each group. Except for the negative control group, the remaining New Zealand rabbits were repeatedly wiped with a blunt surgical blade at about 1 / 3 of the right uterus to create a wound about 2 cm long, until punctate bleeding occurred on the wound. The negative control group only underwent laparotomy without wiping the uterus.

[0063] (3) Placement of materials: For the New Zealand rabbits in the experimental group, an anti-adhesion material about 3 cm long was placed on the wound surface. No product was placed in the positive control group.

[0064] (4) Closing the abdomen: After moistening the abdominal cavity with saline, the incisions in the muscle layer and skin layer of the abdominal wall of all New Zealand rabbits were sutured layer by layer.

[0065] (5) Postoperative care: Penicillin is administered for three days to prevent inflammation. The patient can drink water 12 hours after surgery and eat food the next day. Within 3 days after surgery, 400,000 IU of penicillin is injected intramuscularly twice a day to prevent infection.

[0066] (6) Gross observation: The rabbits were observed 4 weeks after the implantation of the anti-adhesion material. The observations included: the nature and extent of any tissue reaction, such as hematoma, edema, cysts, and other gross findings; the presence, morphology, and location of the implant, including material residues; wound healing, adhesion, material degradation, etc.

[0067] Experimental Example 1 Study on the mechanical properties of anti-adhesion materials

[0068] 1. Experimental Methods

[0069] 1. Determination of breaking strength and elongation at break

[0070] The tensile strength test was performed on a sample with a specification of 54×10 mm. The sample was soaked in saline for 5 min before the test. The upper and lower ends of the sample were fixed on the clamp, and the clamp movement speed was set to 50 mm / min. The tensile machine was started until the sample broke, and the maximum tensile force the sample was subjected to when it broke was recorded as the breaking strength. In the tensile strength test, the ratio of the displacement of the sample when it broke to the original length of the sample was recorded as the elongation at break.

[0071] 2. Determination of bursting strength

[0072] The bursting strength test is carried out on a sample with a specification of 40×40 mm. During the test, the position of the clamp is fixed, and the moving speed of the steel ball push rod is set to 100 mm / min. When setting the stroke, the steel ball push rod should not contact the base after breaking the sample. Place the sample flat in the annular clamp, fix and tighten it. Start the tensile machine and move the steel ball push rod until the sample breaks. Record the steel ball bursting strength of the sample.

[0073] 2. Experimental Results

[0074] This experimental example uses anti-adhesion materials prepared with different decellularization times, and the mechanical property test results are shown in Table 2: The anti-adhesion materials prepared by the present invention have certain mechanical properties. The material prepared under the preferred decellularization time has a breaking strength of 3.15N, a breaking elongation of 25.62%, and a bursting strength of 20.84N.

[0075] Table 2 Relationship between decellularization time and mechanical properties of materials

[0076]

[0077] Experimental Example 2 Study on the Antigen Removal Effect of Anti-adhesion Materials

[0078] 1. Experimental Methods

[0079] The anti-adhesion material used in the present invention is prepared according to the method of Example 1, except that the amount of degreasing solvent used and the decellularization time are different. The specific amount of degreasing solvent used and the decellularization time are shown in Tables 3 and 4.

[0080] The samples were cut into 4×4 mm specimens and tested for host cell residues according to the method specified in YY / T 1794-2021; the DNA residues were tested according to the quantitative PCR method 3407 of the General Rules of Part III of the 2020 edition of the Pharmacopoeia of the People's Republic of China; and the fat residues were tested according to the second method of GB 5009.6-2016.

[0081] 2. Experimental Results

[0082] The experimental results are shown in Tables 3 and 4: when the amount of solvent used for degreasing is 6L, the fat residue of the anti-adhesion material is significantly reduced to 0.9% (dry basis); when the decellularization time is 10-20h, no host cell nucleus remains, and the DNA residue is very small. When the decellularization time is 15h or 20h, the DNA residue is equivalent, about 24ng / g. The above results show that the anti-adhesion material prepared by the present invention has very little fat and DNA residue, no host cell residue, and excellent antigen removal effect.

[0083] Table 3 Relationship between the amount of solvent used for degreasing and the amount of fat residue

[0084]

[0085] Table 4 Relationship between decellularization time and residual DNA / cell content

[0086]

[0087] Experimental Example 3 Study on the biocompatibility of anti-adhesion materials

[0088] 1. Experimental Methods

[0089] The prepared biological anti-adhesion material was evaluated for biocompatibility in accordance with the GB / T 16886 "Biological Evaluation of Medical Devices" series of standards. Specific items included: cytotoxicity test, skin sensitization test, intradermal reaction test, subcutaneous implantation test, pyrogen test, and subchronic systemic toxicity test.

[0090] 2. Experimental Results

[0091] The results show that the biological anti-adhesion material of the present invention has no cytotoxic reaction; no skin sensitization reaction; the final scores of polar extraction and non-polar extraction of the material are both less than 1.0; no abnormal signs were observed in the test animals at each time point during the implantation period; the biological anti-adhesion material has no pyrogenic reaction; no subchronic systemic toxicity; and the thymidine kinase (TK) gene mutation test is negative. Therefore, the biological anti-adhesion material prepared by the present invention has good biocompatibility.

[0092] Experimental Example 4 Study on the adhesion effect of anti-adhesion materials

[0093] 1. Experimental Methods

[0094] The adhesion effects of New Zealand rabbits with postoperative abdominal adhesion were observed in each group.

[0095] The model rabbits underwent surgery again at four weeks to evaluate the adhesion in the abdominal cavity. The adhesion of each group of New Zealand rabbits was scored according to the modified American Society for Reproductive Medicine adhesion grading standard:

[0096] ① The nature and extent of adhesion (0-6 points, 0 means no adhesion)

[0097]

[0098] ② Toughness score (0-3 points, 0 means no toughness)

[0099]

[0100] 2. Experimental Results

[0101] The results are as follows Figure 2As shown: Regarding the negative control group, the rabbit was opened again 4 weeks later, and the rabbit's uterus and bladder had mild membranous adhesions, the adhesion range was <25%, and it could be separated by traction. Regarding the positive control group, the rabbit was opened again 4 weeks after modeling, and the rabbit's uterus and bladder had moderate membranous adhesions, the adhesion range was ≥51%, and it could be separated by blunt traction. The wound was basically healed, and no infection or ulceration occurred. Regarding the experimental group, the uterine bleeding area just implanted with the anti-adhesion material was completely covered by the material; 4 weeks after implantation, the anti-adhesion material in the uterus was completely degraded, the uterus and the abdominal wall had mild membranous adhesions, the adhesion range was <25%, and it could be separated by traction. The wound healed well, and no infection or ulceration occurred. The results show that the anti-adhesion material provided by the present invention has a good anti-adhesion effect and is conducive to the healing of postoperative wounds.

[0102] Experimental Example 5 Study on the degradation properties of biological anti-adhesion materials

[0103] 1. Experimental Methods

[0104] 1. In vitro degradation experiment

[0105] The biological anti-adhesion material sample was cut into 25×25 mm specimens for degradation test. About 0.1 g (recorded as m0) of the sample was weighed and added to a 60 mm culture dish. 5 mL of type I collagenase solution with a concentration of 10 mg / mL was carefully added to the culture dish and mixed to ensure that the sample was at the bottom of the culture dish. After being placed in a 37°C incubator at a constant temperature for 2 h, the supernatant was removed as much as possible with a pipette and the enzyme solution was added again. After being placed at a constant temperature for another 4 h, the sample was taken out of the culture dish and placed in a 50 mL centrifuge tube. About 40 mL of purified water was added, and the residue was cleaned with ultrasound for 5 min. Centrifugation (centrifuge parameters: 6000 rpm, 10 min) was repeated for 3 times. The precipitate was collected in a weighing bottle with constant weight and dried at 105°C to constant weight. The weight was recorded as m1. Three parallel samples were measured at the same time, and the degradation rate was calculated respectively.

[0106] 2. In vivo degradation experiment

[0107] The model rabbits were operated on again 4 weeks later, and the in vivo degradation effect of postoperative abdominal adhesions in each group of New Zealand rabbits was observed.

[0108] 2. Experimental Results

[0109] 1. In vitro degradation performance

[0110] The results of in vitro degradation experiments showed that under the action of type I collagenase, the degradation rate of the biological anti-adhesion material could reach more than 30% after being cultured at 37°C for 4 hours.

[0111] 2. In vivo degradation performance

[0112] In vivo degradation experiments Figure 2Shown: The anti-adhesion material can be completely degraded 4 weeks after implantation in the body.

[0113] The above experimental results show that the anti-adhesion material prepared by the present invention has certain mechanical properties, excellent antigen removal effect, good anti-adhesion effect and wound healing promotion effect, excellent degradation performance, and can be completely degraded in vivo within 4 weeks.

[0114] It can be seen from the above embodiments and experimental examples that the present invention provides a degradable, low-immunogenic biological anti-adhesion material. The porcine small intestine is pretreated, deantigenized, and freeze-dried to obtain a decellularized matrix material. The preparation process is stable and the product is easy to store. The material has suitable mechanical properties, excellent deantigenization effect, and a DNA residue of 24ng / g. When the material is used for postoperative adhesion prevention in the abdominal cavity, it has good biocompatibility and low immunogenicity, and will not cause obvious postoperative immune response after implantation; it has good biomechanical properties and good fitting performance, and does not require suture fixation after fitting the wound. It has degradable absorbability and can be completely degraded within four weeks. It has a good anti-adhesion effect in animal abdominal cavity anti-adhesion and is an excellent degradable biological anti-adhesion material. It has promoted the application of decellularized matrix materials in implantable medical materials, and the prospects are good.

Claims

1. A biodegradable low-immunogenic biological anti-adhesion material, characterized in that: It is prepared by a method comprising the following steps: Step 1, taking the small intestinal submucosal tissue of the animal, washing, inactivating, and mechanically treating it; Step 2, washing the material of step 1, soaking it in an organic solvent and an acetic acid aqueous solution respectively, and then washing it to obtain a decellularized matrix fresh film; Step 3, freeze-drying the acellular matrix fresh film to obtain; The immersion time in the acetic acid aqueous solution is 15 hours; the concentration of the acetic acid aqueous solution is 1.8-2.2 mol / L; The freeze-drying procedure is: pre-freeze to -50~-40°C under non-vacuum, and keep warm for 0.8-1 minute; then start the vacuum, adjust the temperature to -40~-35°C, and keep warm for 0.8-1 minute; adjust the temperature to -30~-25°C, and keep warm for 0.8-1 minute; adjust the temperature to -22~-18°C, and keep warm for 0.8-1 minute; adjust the temperature to -10~-5°C, and keep warm for 0.8-1 minute; adjust the temperature to -2~2°C, and keep warm for 0.8-1 minute; adjust the temperature to 10~15°C, and keep warm for 0.8-1 minute; adjust the temperature to 20~25°C, and keep warm for 0.8-1 minute; adjust the temperature to 25~35°C, and keep warm for 0.8-1 minute.

2. The biological anti-adhesion material according to claim 1, characterized in that: The organic solvent is a mixed solvent of methanol and chloroform in a volume ratio of 1:1-1.2, the volume of the organic solvent is 2-6L, and the soaking time in the organic solvent is 120±10 minutes.

3. The biological anti-adhesion material according to claim 2, characterized in that: The volume of the organic solvent is 6L.

4. The biological anti-adhesion material according to claim 1, characterized in that: In step 1, the cleaning is performed by washing with water, the inactivation is performed by soaking in a peracetic acid solution having a mass fraction of 2.9% to 3.2% for 90 to 120 minutes, and the mechanical treatment is performed by mechanically removing the muscle layer and the serosal layer; And / or, in step 2, the cleaning is performed by washing with water and ultrasonically treating the mixture at a power of 280-300 W for 20-60 minutes.

5. The biological anti-adhesion material according to claim 1, characterized in that: The biological anti-adhesion material has a DNA residue of 22.9-85.2 ng / g, a fat residue of 0.85-8.8% by mass, a breaking strength of 1.9-3.3N, a breaking elongation of 17.3-26.9N, and a bursting strength of 14.3-21.9N.

6. The method for preparing the biological anti-adhesion material according to any one of claims 1 to 5, characterized in that: The steps include: Step 1, taking the small intestinal submucosal tissue of the animal, washing, inactivating, and mechanically treating it; Step 2, washing the material of step 1, soaking it in an organic solvent and an acetic acid aqueous solution respectively, and then washing it to obtain a decellularized matrix fresh film; Step 3, freeze-drying the acellular matrix fresh film to obtain; The immersion time in the acetic acid aqueous solution is 15 hours; the concentration of the acetic acid aqueous solution is 1.8-2.2 mol / L; The freeze-drying procedure is: pre-freeze to -50~-40°C under non-vacuum, and keep warm for 0.8-1 minute; then start the vacuum, adjust the temperature to -40~-35°C, and keep warm for 0.8-1 minute; adjust the temperature to -30~-25°C, and keep warm for 0.8-1 minute; adjust the temperature to -22~-18°C, and keep warm for 0.8-1 minute; adjust the temperature to -10~-5°C, and keep warm for 0.8-1 minute; adjust the temperature to -2~2°C, and keep warm for 0.8-1 minute; adjust the temperature to 10~15°C, and keep warm for 0.8-1 minute; adjust the temperature to 20~25°C, and keep warm for 0.8-1 minute; adjust the temperature to 25~35°C, and keep warm for 0.8-1 minute.

7. Use of the biological anti-adhesion material according to any one of claims 1 to 5 in the preparation of implantable medical materials, wherein the implantable medical materials include abdominal repair patches, oral repair patches, pelvic floor repair patches, and hernia repair patches.

8. A biodegradable low-immunogenic biorepair patch, characterized by: The biological anti-adhesion material is prepared by taking the biological anti-adhesion material as any one of claims 1 to 5 as an active substance and adding pharmaceutically acceptable auxiliary materials or auxiliary components.

Citation Information

Patent Citations

  • A biological anti-adhesion material, its preparation method and its application

    CN106983918B

  • Biological membrane as well as preparation method and application thereof

    CN118987351A